2004
DOI: 10.1161/01.atv.0000147406.00871.b3
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Labile Iron Modulates Adhesion of Human Monocytes to Human Endothelial Cells

Abstract: Objective-Elevated iron stores and high plasma iron concentration have been linked to an increased risk of atherosclerosis.Iron may thereby affect the interaction of monocytes to endothelium, an initial event in the formation of atherosclerotic plaques. Methods and Results-Addition of 10 mol/L non-transferrin-bound iron to the incubation medium caused a 2-fold increase in monocyte adhesion to human umbilical vein endothelial cells (HUVECs). A concordant increase in the expression of the following adhesion mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 58 publications
(41 reference statements)
1
52
2
Order By: Relevance
“…Experimental cell culture studies had shown that addition of NTBI to human endothelial cell culture increase the surface expression of adhesion molecules and also increase the monocyte adherence to endothelium [95,96]. These consequences can be corrected by addition of iron chelators like desferrioxamine and dipirydyl, which decrease expression of adhesion molecules and monocyte adherence [95,96].…”
Section: Role Of Iron In Cardiac Diseasementioning
confidence: 99%
“…Experimental cell culture studies had shown that addition of NTBI to human endothelial cell culture increase the surface expression of adhesion molecules and also increase the monocyte adherence to endothelium [95,96]. These consequences can be corrected by addition of iron chelators like desferrioxamine and dipirydyl, which decrease expression of adhesion molecules and monocyte adherence [95,96].…”
Section: Role Of Iron In Cardiac Diseasementioning
confidence: 99%
“…In cell culture models, the addition of NTBI to human endothelial cell cultures increases surface expression of adhesion molecules (101,102) and also increases monocyte adherence to the endothelium. These abnormalities can be corrected by the addition of iron chelators such as desferoxamine and dipirydyl.…”
Section: The Role Of Iron In Endothelial and Vascular Diseasementioning
confidence: 99%
“…These abnormalities can be corrected by the addition of iron chelators such as desferoxamine and dipirydyl. Such an addition decreases expression of adhesion molecules and monocyte adherence (101)(102)(103). In human studies of end-stage renal disease patients, intravenous iron therapy has been shown to increase vascular and systemic oxidative stress (104 -106), promote atherosclerosis (106), and increase the risk of arterial thrombosis (105).…”
Section: The Role Of Iron In Endothelial and Vascular Diseasementioning
confidence: 99%
“…Furthermore, it consists of a transmem-brane region and a very short cytoplasmic tail of only 28 aa. Its role as receptor within the leukocyte-adhesion cascade is very well recognized (22)(23)(24)(25)(26); it was shown that surface ICAM-1 levels on endothelial cells are inducible by cytokines (mostly TNF-a and IL-1b), bacterial LPSs, and redox-sensitive mechanisms (27)(28)(29)(30). ICAM-1 can also be found on the surface of monocytes; however, until now, its known function is limited to Ag presentation to MHC class II-restricted T cells (31,32).…”
mentioning
confidence: 99%